Edukasi Pembuatan Pupuk Organik Cair dan Bokashi sebagai Upaya Mitigasi Pencemaran Limbah Organik - Refli, Refli; Dima, Alfred O M; Bana, Joice J; Nurwiana, Ida; Prasetyo, Dwi; Nalle, Agus Arnold; Lawa, Yosep; Nenotek, Petronella Syahyanti; Nahas, Agustina Ethin; Kaho, Uly Jonathan Riwu (Prima Abdika: Jurnal Pengabdian Masyarakat, 2025)
The amount of organic waste continues to increase along with the growing population and changing consumption patterns. This will impact the rise of greenhouse gases and the decline in environmental quality. Therefore, community service activities aim to provide education on processing organic waste into useful and environmentally friendly products in the form of liquid organic fertilizer (LOF) and bokashi as an effort to mitigate environmental pollution. The educational activities are conducted using the participatory rural approach (PRA) method, where participants are directly involved in the production of LOF and bokashi. The activities are divided into four main stages: observation, training and mentoring implementation, and activity evaluation. The target of community service is the Betlehem Oesapa Barat congregation, which is organized into the Bethlehem Farmers Group consisting of 25 people. The evaluation results show that community activities with the PRA approach have an effectiveness level of up to 96% in transferring waste management knowledge and skills to participants. This is supported by the change in knowledge about making LOF and bokashi from 8% before the educational activities to 92% by the end of the activities. About 96% of participants stated that the activities were beneficial to them, with 92% of participants wanting to independently implement the results of the activities. The follow-up to these activities includes continuous monitoring and evaluation, as well as further development related to the use of LOF and bokashi in the horticultural cultivation of the farmers' group. Additionally, efforts will be made to expand the reach to the congregation and community by the community service team of the Postgraduate program The University of Nusa Cendana in order to create a society that is aware and cares about the environment and actively participates in mitigating waste pollution in the future.